Distinct Epidemiology and Clinical Consequence of Classic Versus Rare EGFR Mutations in Lung Adenocarcinoma. Issue 5 (May 2015) - Lohinai, Zoltan; Hoda, Mir Alireza; Fabian, Katalin; Ostoros, Gyula; Raso, Erzsebet; Barbai, Tamas; Timar, Jozsef; Kovalszky, Ilona; Cserepes, Mihaly; Rozsas, Anita; Laszlo, Viktoria; Grusch, Michael; et al.
<x xml:space="preserve">Abstract</x> Introduction: Although classic sensitizing mutations of epidermal growth factor receptor (EGFR) are positive predictive markers for EGFR tyrosine kinase inhibitors (TKIs) in lung adenocarcinoma, there are rare EGFR mutations with unknown epidemiology and influence on prognosis and TKI response. Methods: Eight hundred and fourteen lung adenocarcinoma patients with KRAS and/or EGFR mutation analyses for TKI therapy indication were identified. Six hundred and forty-five patients were included in the epidemiological analysis. The clinical outcome was analyzed in 419 advanced-stage patients with follow-up data. Results: Four hundred and eighty (59%) KRAS/EGFR double wild-type, 216 (27%) KRAS mutant, 42 (5%) classic, 49 (6%) rare, and 27 (3%) synonymous EGFR mutant cases were identified. Twenty previously unpublished non-synonymous mutations were found. Rare EGFR mutations were significantly associated with smoking (vs. classic EGFR mutations; p = 0.0062). Classic EGFR mutations but not rare ones were independent predictors of increased overall survival (hazard ratios, 0.45; 95% confidence intervals, 0.25–0.82; p = 0.009). TKI therapy response rate of patients harboring classic EGFR mutations was significantly higher (vs. rare EGFR mutations; 71% vs. 37%; p = 0.039). Patients with classic or sensitizing rare (G719x and L861Q) EGFR mutations had significantly longer progression-free survival when compared with the remaining rare mutation cases (12 vs. 6.2 months; p = 0.048). Conclusions: The majority of rare EGFR mutations was associated with smoking, shorter overall survival, and decreased TKI response when compared with classic EGFR mutations. However, studies characterizing the TKI sensitizing effect of individual rare mutations are indispensable to prevent the exclusion of patients with sensitizing rare EGFR mutations who may benefit from anti-EGFR therapy.